Moisture dynamics and irrigation modelling in apple (Malus domestica) trees using CROPWAT model in temperate region of India - KUMAR, ROHITASHW; NISSA, RUHUL; KUMAR, MUKESH (The Indian Journal of Agricultural Sciences, 2018)
A quantitative study of water transport in the soil-root system is an important aspect for optimum irrigation scheduling and sound water management. The present study was conducted for high density apple (Malus domestica Borkh.) (var. Silver Spur) orchard in temperate region of Kashmir valley, India to evaluate moisture uptake/depletion at different depth of root zone.Soil moisture depletion at different root depth was determine dusing CROPWAT model. The maximum depletion of moisture took place in the top 16 cm layer of crop root zone. The crop coefficient values were modified for local agro-climatic conditions using the procedure outlined by FAO. The Modified crop coefficient (Kc) value for different growth stages of Kc ini, Kc mid and Kc end were found 0.5, 1.13 and 0.76, respectively. The crop water requirement was determined using CROPWAT model and compared with field observed value.The results showed that the model predicted the crop evapotranspiration with reasonable error statistics with RMSE; 0.19 mm/ day, R2; 0.97 and percent error; 10.90. The CROPWAT model can be used for estimating crop water requirement for high density apple crop for irrigation scheduling.